An Uneven Recovery : Taking the Pulse of Latin America and the Caribbean Following the Pandemic - 2021 LAC High Frequency Phone Surveys - United Nations Development Program (UNDP); World Bank (World Bank, Washington, DC, 2022)
To continue monitoring how the Coronavirus (COVID-19) pandemic has affected the welfare of households in the region, the World Bank and UNDP have joined forces in the implementation of a second phase of High-Frequency Phone Surveys (HFPS) in Latin America and the Caribbean. The survey, collected between May and July 2021, takes the socio-economic pulse of households and measures the wellbeing of the region a year and a half into the pandemic. This note presents the emerging results in the areas of labor markets, income and food security, education, gender, health, and access to digital and banking services.